2009
DOI: 10.3151/jact.7.217
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Capability of Fibre Reinforced Cementitious Composites

Abstract: In order to investigate the self-healing capability of fibre reinforced cementitious composites (FRCC), mechanical properties and surface morphology of crack in FRCC were studied. Three types of FRCC specimens containing (1) polyethylene (PE) fibre, (2) steel cord (SC) fibre, and (3) hybrid fibres composite (both of PE and SC) were prepared. These specimens, in which cracks were introduced by tension test, were retained in water for 28 days. The self-healing capability of the specimens was investigated by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
149
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(153 citation statements)
references
References 18 publications
2
149
0
2
Order By: Relevance
“…Yang et al (2009) also reported on the recovery of stiffness in ECC under wet and dry cycles. Homma et al (2009) investigated the self-healing phenomena of different types of FRCCs including a hybrid fiber system, and they confirmed the recovery of water tightness and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2009) also reported on the recovery of stiffness in ECC under wet and dry cycles. Homma et al (2009) investigated the self-healing phenomena of different types of FRCCs including a hybrid fiber system, and they confirmed the recovery of water tightness and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…While Heap et al (2013) showed that the water permeability of concrete increases significantly with the progress of fracturing, it is also possible that the sealing of existing fractures and pores affects the permeability of concrete. So far, various reports on the fracture sealing of concrete have been published (e.g., Jacobsen and Sellevold 1996;Hearn and Morley 1997;Hearn 1997;Edvardsen 1999;Reinhardt and Jooss 2003;Granger et al 2007; Van der Zwaag 2007;Homma et al 2009;Qian et al 2009;Yang et al 2009;Ahn and Kishi 2010;Wu et al 2012;Fukuda et al 2012;Fukuda et al 2013). Among this literature, Edvardsen (1999) showed that the sealing of a fracture occurs by the precipitation of calcium carbonate, generated from CO 3 2− in the water and Ca 2+ in the cement paste, and that the fracture aperture and applied water pressure significantly affect the sealing, while the types of cement and aggregate and the hardness of the water have no influence on the sealing rate.…”
Section: Introductionmentioning
confidence: 99%
“…For concrete of sufficient age, the formation of calcium carbonate primarily occurs (e.g. Jacobsen and Sellevold 1996;Hearn and Morley 1997;Hearn 1997;Edvardsen 1999;Van der Zwaag 2007;Homma et al 2009;Qian et al 2009;Yang et al 2009). While Heap et al (2013) showed that the water permeability of concrete increases significantly with the progress of fracturing, it is also possible that the sealing of existing fractures and pores affects the permeability of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that self-healing was not as robust as that observed in some experimental results carried out under controlled laboratory conditions, though the self-healing in the natural environment was promising. Homma et al (2008) investigated the self-healing capability of FRCC by microscope observation, water permeability test, tension test and backscattered electron image analysis. They prepared specimens with water/binder ratio of 0.45, containing three different types of fiber (i.e.…”
Section: Engineering With Fiber Reinforcementmentioning
confidence: 99%